Stress Field Characterization in Rotating Anisotropic Polypropylene Cylinders: Analytical Modeling and SVR Validation - Kayıran, Hüseyin Firat (International Journal of Sustainable Development Goals, 2025)
In this study, the elastic stress distribution in a rotating cylinder composed of polypropylene (PP) material was investigated using analytical formulations and parametric evaluations. Tangential and radial stresses, as well as radial displacements, were calculated under varying anisotropy parameters to observe their influence on the mechanical behavior. The stress components were derived by incorporating both elastic and centrifugal effects under steady-state rotational motion. The results were evaluated in terms of the Von Mises yield criterion to identify critical stress zones. Graphical representations of stress and displacement distributions were presented for different anisotropy levels. An equilibrium check was also conducted to verify the accuracy of the stress fields. To enhance reliability, the analytically obtained radial stress values were also validated using Support Vector Regression (SVR), demonstrating strong agreement and underscoring the potential of machine learning techniques in predicting complex stress distributions. The study highlights that increasing rotational speed leads to a rise in tangential stress while the radial stress tends to decrease near the boundaries. These findings underline the importance of considering anisotropic behaviour in polymer-based rotating systems. Moreover, the implemented framework demonstrates the potential integration of computational and analytical approaches for stress prediction in engineering-grade thermoplastic materials.